Prevalence, capsular types, antimicrobial resistance and risk factors associated with pneumococcal carriage among children after long-term 10-valent pneumococcal conjugate vaccine use in Brazil. Issue 19 (5th May 2023) - Fortuna, Letícia B.D.P.; Miranda, Filipe M.; Antunes, Isa M.F.; Silva, Amanda B.; Cabral, Amanda S.; Dolores, Ítalo M.; Cardoso-Marques, Nayara T.; Teixeira, Lúcia M.; Neves, Felipe P.G.
Abstract: Background: The 10-valent pneumococcal conjugate vaccine (PCV10) was introduced for childhood vaccination in Brazil's National Immunization Program in 2010. After nine years of PCV10 use, we investigated the carriage prevalence, capsular types, antimicrobial resistance and risk factors among children living in Niterói city, RJ, Brazil. Methods: Between September and December 2019, we conducted a cross-sectional study and recruited children under 6 years of age. Antimicrobial susceptibility was evaluated by the disk-diffusion method and MICs to beta-lactams and macrolides were determined by E-test®. Capsular types were deduced by multiplex PCR. Logistic regression was used to predict risk factors for pneumococcal carriage. Results: Seventy-five (17.4%) of the 430 children were pneumococcal carriers. The most frequent capsular types were 6C/D (14.7%), 11A/D (13.3%), and 23B (9.3%). PCV10 serotypes represented 5.3%. All isolates were susceptible to levofloxacin, linezolid, rifampicin, and vancomycin. Penicillin non-susceptible pneumococci (PNSP) made up 37.3%, with penicillin and ceftriaxone MICs ranging from 0.12 to 4.0 μg/ml and 0.064–4.0 μg/ml, respectively. Of the 19 (25.3%) erythromycin-resistant (ERY-R) isolates (macrolide MICs of 6 to >256 μg/ml), most had the cMLSB phenotype (84.2%) and carried the erm (B) gene (73.7%). We detected 17 (22.6%) multidrug-resistant (MDR) isolates, strongly associated with serotype 6C/D. Presence of any symptoms, chronic diseases, childcare center attendance, living with young siblings, slum residence, and unstable income were predictors of pneumococcal carriage. Conclusions: Long-term universal childhood use of PCV10 has nearly eliminated carriage with PCV10 serotypes, but the high frequency of MDR isolates, especially associated with serotype 6C/D, remains a concern. Replacing PCV10 with PCV13 should reduce the proportion of ERY-R isolates and PNSP by at least 14% and 18%, respectively.